Effect of Nitrogen Fertilization and Inoculation with Bradyrhizobium japonicum on Nodulation and Yielding of Soybean - Ewa Szpunar-Krok; Dorota Bobrecka-Jamro; Wojciech Pikuła; Marta Jańczak-Pieniążek (Agronomy, 2023)
Legumes’ nutrition relies on two sources of nitrogen (N): mineral N from soil, and biological N fixation (BNF). The aim of this study was to verify the effect of bacterial inoculation, as well as to compare it with the effect of different mineral N fertilization on the main nodulation characteristics, yield components and seed yield of two soybean (Glycine max (L.) Merr.) cultivars in the conditions of south-eastern Poland. A randomized block design was used with four replications and combining the application rates of mineral N (0, 30 and 60 kg·ha−1), and seed inoculation with Bradyrhizobium japonicum (HiStick® Soy and Nitragina) were applied for two soybean cultivars (Aldana, Annushka). It has been shown that inoculation of B. japonicum increases the nodulation on plant roots, yield components and seed yield, but no significant effect of the bacterial preparation used on the seed yield was observed. The application of 30 kg N·ha−1 did not result in a significant reduction in the number and weight of nodules, including on the main root and lateral roots, compared to seeds inoculated and not fertilized with N, as observed under a dose of 60 kg N·ha−1, but resulted in an increase in the number of pods and the number and weight of seeds per plant. For both soybean cultivars, the best combination was nitrogen fertilization at 30 kg N·ha−1 and seed inoculation with B. japonicum, regardless of the bacterial preparation used.